Herder und Ratzel: Zwei Extreme, ein Paradigma? - Schultz, Hans-Dietrich (ERDKUNDE, 1998)
On the one hand, Ratzel’s position is understood as a theory that does not explain the capitalistic modernity via determination by nature, and on the other hand as a backwards-orientated geo-deterministic one. As such, his conception of geography is either interpreted as breaking with the classical conception of geography or as continuing in this tradition, which was essentially inspired by Herder. From Herder’s perspective, the most natural state represents one nation with one national character under the dominion of one climate. The outer frame is shaped by the topography of the country, whereas the seclusion of nations from each other is supported by their entire natural environment. This concept was taken up by the classical school of geography, which regarded it as one of their tasks to figure out the degree of correspondence between the existing political demarcation and the nature-given borders. What had once been cared for by the invisible hand of nature had from now on to be explained by scientists and transferred to real existence by politics: the congruence of natural area and state. Yet, this is only valid for the phase of nation-building, not for the period of imperialist nationalism. Ratzel was exactly the one who adapted the geographical paradigm to the new circumstances. Even though relying on the concept of natural areas, he replaced their original position as equally ranked by building hierarchies, and thus abolishing the identity of nation and state - Herder’s idea. This paved the way for the law of expanding areas resulting from Ratzel’s notion of a permanent struggle of nations for the scanty space on earth. Even though the shape of the earth’s surface plays an important role in both concepts, its function is entirely different. While it separates and limits nations and states in the classical paradigm, it provokes expansion from Ratzel’s point of view. The utopian scheme of everlasting peace transforms into a theory of everlasting war. In this respect Ratzel’s theory was a source of inspiration for the ideology of Lebensraum of the Third Reich. The shift to the paradigm of race as the decisive power in history is already inherent in his theory.